Ombudsmen in the United Kingdom - Yardley, Sir David (1995)
"The author traces evolution of Ombudsman system in the U.K. describes its present system of Parliamentary Commissioner for Administration, along with other ombudsmen related to government functions, and then gives his comments on functioning of ombudsmen in the country. He also points out future developments in the system in the U.K."
Keywords: Ombudsman - Great Britain; Ombudsman